Short-run impact of captive supplies on fed cattle prices - J. Mintert; R. Jones; F. Brazle; Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 1992)
Factors affecting western Kansas fed cattle prices during May through November 1990 were investigated. In particular, the impact of changes in captive cattle supplies on cash prices was examined. The term captive cattle supplies refers to cattle procured by a packer well in advance of slaughter. Captive supplies take one of three forms: 1) packer-owned cattle, 2) cattle procured on forward contracts, and 3) cattle procured under formula price (or marketing) agreements. Captive supplies were defined as cattle procured under forward contracts or formula price agreements, because data on packer-owned cattle were unavailable. Over the May through November 1990 period as a whole, the presence of captive cattle supplies was associated with an average reduction in western Kansas cash market transaction prices of about 0.15/cwt.
Keywords: Cattlemen& #x27; s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Cattle marketing; Cattle prices; Captive supplies